Operating experience with nuclear power sta tions in member states in 2007 (Vienna, Austria : International Atomic Energy Agency, 2008)
Useful to everyone concerned with Nuclear Power reactors
This report is the thirty-ninth in the Agency's series of annual rep orts on operating experiences with nuclear power stations in Member Sta tes.
Contains historical summary performance and outages during the lifet imeof individual plants and six figures illustrating worldwide performa nce statistical data
Also available in CD-ROM
Keywords: Nuclear reactors; Nuclear power plants -- Reporting